Ethics in Tax Practice. - Raby, William L. (The Accounting Review, 1966)
This article examines the fundamental ethical rule in tax practice at the level of personal ethics in the U.S. in 1966. This rule states that the tax practitioner must allow the client to make the final decisions. The practitioner has no right to substitute his scale of values for that of the client. Beyond that, the practitioner must recognize a positive responsibility not to provide false or misleading information to the government. This responsibility is imposed on him by Circular 230 and by the Code of Professional Ethics of the American Institute of Certified Public Accountants.